2013
DOI: 10.1186/1749-799x-8-13
|View full text |Cite
|
Sign up to set email alerts
|

A non-invasive biomechanical device and treatment for patients following total hip arthroplasty: results of a 6-month pilot investigation

Abstract: BackgroundThe purpose of the study was to examine the effect of a foot-worn biomechanical device on the clinical measurements and gait patterns of patients with total hip arthroplasty (THA).MethodsNineteen patients, up to 3 months post-THA, were enrolled to the study. Patients underwent a computerized gait analysis to calculate spatiotemporal parameters and completed the Western Ontario and McMaster Universities osteoarthritis index and the SF-36 health survey. Patients then began therapy with a non-invasive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…It must address wider perspectives of generalized neuromuscular control. In recent years, several publications regarding the effect of a novel non-invasive biomechanical device for different musculoskeletal disorders have been published [12][13][14][15]. A unique foot-worn device enables the relocation of the center of pressure [16] while training neuromuscular control [17].…”
Section: Introductionmentioning
confidence: 99%
“…It must address wider perspectives of generalized neuromuscular control. In recent years, several publications regarding the effect of a novel non-invasive biomechanical device for different musculoskeletal disorders have been published [12][13][14][15]. A unique foot-worn device enables the relocation of the center of pressure [16] while training neuromuscular control [17].…”
Section: Introductionmentioning
confidence: 99%
“…footwear device for participants with unilateral/bilateral hip osteoarthritis (Solomonow-Avnon et al, 2017) or following hip arthroplasty (Segal et al, 2013). These studies provided very low certainty evidence for improvement over time.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with knee OA that have been previously treated with this biomechanical device have shown reductions in knee adduction and flexion moments during barefoot walking, which were accompanied by significant reductions in pain and subsequent improvements in function and quality of life [31,38,48]. Previous studies have also suggested a positive clinical effect for the device when addressing other musculoskeletal conditions such as degenerative meniscal tear, post total knee replacement, hip OA, post total hip replacement and in patients with chronic nonspecific low back pain [49][50][51][52][53][54].…”
Section: Methodsmentioning
confidence: 96%